A Randomized, Prospective Study to Compare the Efficacy and Safety of Omega-3 Fatty Acids as Additional Therapy to Methotrexate versus Methotrexate Monotherapy in the Management of Moderate to Severe Plaque Psoriasis - Ankita Bedwal; Kavitha Rajarathna; Revathi T.N. (Universitas Padjadjaran, Indonesia, 2021)
Psoriasis is a chronic, inflammatory, hyperproliferative, immune-mediated skin disorder, having a prevalence of 0.44-2.8% in India. Methotrexate is a widely used systemic regimen for moderate to severe psoriasis. Supplementation of omega-3 fatty acids has decreased the severity of the disease in some studies. This study aimed to assess the efficacy and safety of omega-3 fatty acids as an add-on to methotrexate versus methotrexate monotherapy in patients with moderate to severe plaque psoriasis. A total of 40 patients with moderate to severe plaque psoriasis were recruited in the study and randomized into two groups of 20 patients each. Group O received omega-3 fatty acids as add-on to methotrexate and Group M received methotrexate monotherapy. Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI), Physician’s Global Assessment (PGA) were assessed at baseline, 4 weeks, 8 weeks and 12 weeks of treatment. The adverse events were assessed throughout the study period. There was a significant decrease in PASI and DLQI scores from baseline to end of 12 weeks in both groups (p<0.001) but the difference between the two groups was not significant (p>0.05). A higher number of patients had a PGA score of 0 or 1 at the end of 12 weeks in Group O (60%) as compared to Group M (40%) but the difference between the groups was not significant (p=0.34). The treatment was well tolerated in both the groups, with most common adverse events being nausea, diarrhea and epigastric pain. This study showed that the treatment in both the groups was equally effective in decreasing the severity of psoriasis and was well tolerated.